COMPARISON OF THE RULES OF NAHWU BASHRAH AND KUFAH SCHOOLS A STUDY OF THE ANALYSIS OF QIYAS AND SIMA’I IN DETERMINING I’RAB - Mahdi, Muhammad (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
Nahwu (Arabic grammar) is a crucial branch of Arabic linguistics that has significantly developed through two main schools: Basrah and Kufah. These schools offer differing approaches in establishing grammatical rules, particularly in the application of Qiyas (analogy) and Sima’i (oral transmission). The Basrah school, pioneered by Sibawaih, emphasizes a rational and structured method through Qiyas, while the Kufah school, represented by Al-Kisa’i and Al-Farra’, relies more on linguistic evidence derived from native Arabic usage (Sima’i). This study employs a qualitative descriptive method using a library research approach to examine differences in i’rab (grammatical inflection) rules between the two schools. The findings reveal that these differences are not only methodological but also influenced by social, geographical, and political factors. Specific examples include distinctions in assigning i’rab for mubtada’ and khabar, forms in dual and plural nouns, and the role of ‘amil in maf’ul constructions.